Educational Facilities: The Impact and Role of the Physical Environment of the School on Teaching, Learning and Educational Outcomes - (:unkn) unknown (My University, 1994)
The quality of the educational environment is rapidly diminishing due to the plethora of social and economic problems plaguing urban communities. Due to this crisis, the physical infrastructure of school systems is being virtually ignored. The author addresses the impact of physical infrastructures on education and the impact of the school building on student achievement. Finally, the author synthesizes and builds upon existing models developed within several disciplines to direct further applied research on educational environments.